A digital voice/data telephone/ Mohd. Afendi Abdul Razak - Abdul Razak, Mohd. Afendi (1991)
This report is about the project of designing digital voice/data telephone. In Chapter 1 of the report will discuss on the general description of the digital telephone and voice/data system. Chapter 2 elaborates on the advantages and disadvantages of digital system over analog system. The next chapter (Chapter 3), describe the voice digitization and coding scheme used in voice/data system. Subsequently, Chapter 4 will touches on project design which will elaborate on the design of multiplexer and digital telephones. The test and the result of the project will consequently be highlighted in the proceeding chapter.